Rediscovering the unusual Cancellus makrothrix Stebbing, 1924 (Crustacea: Decapoda: Diogenidae) in the “Great African Seaforest” - Landschoff, Jannes; Lemaitre, Rafael (Zootaxa, 2024)
The rare diogenid hermit crab Cancellus makrothrix Stebbing, 1924, previously known from only a few specimens collected a century ago from Algoa Bay, South Africa, has been found to be common in the kelp forest known as the “Great African Seaforest”, and rocky reefs, of False Bay, South Africa. This poorly known species, considered “aberrant” by some carcinologists, is one of 17 known in the genus Cancellus H. Milne Edwards, 1836, and the only of the genus known to occur in the coast of southern Africa. Cancelllus makrothrix lives in gastropod shells, whereas all other congenerics live in a variety of petricolous dwellings that are either excavated or worn away into cylindrical cavities. The newly collected material of C. makrothrix in South Africa, together with the study of historical museum specimens has made possible the detailed redescription and taxonomic discussion of this species presented herein, using full illustrations, photographs, and microCT scans. For future reference, the molecular CO1 genetic barcode is reported. A lectotype is selected from Stebbing’s original syntype material found to consist of two specimens: a female of which only several appendages remain, in the Natural History Museum, London, and a male, illustrated in the original description, in the Iziko South African Museum, Cape Town. Taxonomic remarks, comments on biological oddities, brief in situ and laboratory observations of live specimens, and a map summarizing the world distribution of species of Cancellus, are included.